Ubiquitin-specific peptidase 8 regulates the trafficking and stability of the human organic anion transporter 1 - Zhang, Jinghui; Liu, Chenchang; You, Guofeng (Biochimica et biophysica acta. General subjects, 2020)
Background Organic anion transporter 1 (OAT1) plays a vital role in avoiding the potential toxicity of various anionic drugs through the involvement of kidney elimination. We previously demonstrated that ubiquitin conjugation to OAT1 led to OAT1 internalization from cell surface, followed by degradation. Ubiquitination is a dynamic process, where deubiquitination is catalyzed by a class of ubiquitin-specific peptidases. Methods The role of ubiquitin-specific peptidase 8 (USP8) in hOAT1 function, expression and ubiquitination was assessed by conducting transporter uptake assay, biotinylation assay and ubiquitination assay. Results We demonstrated that USP8 overexpression in hOAT1-expressing cells led to an increased hOAT1 transporter activity and expression, which correlated well with a reduced hOAT1 ubiquitination. Such phenomenon was not observed in inactive USP8 mutant-transfected cells. In addition, the knockdown of endogenous USP8 by USP8-specific siRNA resulted in an increased hOAT1 ubiquitination, which correlated well with a decrease in hOAT1 expression and transport activity. Biotinylation experiments demonstrated that USP8-induced increase in hOAT1 expression and transport activity occurred through a deceleration of the rates of hOAT1 internalization and degradation. Conclusions These results indicated the regulatory role of USP8 in OAT1 function, expression, trafficking, and stability. General significance USP8 could be a new target for modulating OAT1-mediated drug transport. [Display omitted] •USP8 overexpression increased OAT1 function while reduced OAT1 ubiquitination.•USP8 knockdown decreased OAT1 function while enhanced OAT1 ubiquitination.•USP8 overexpression decelerated the rates of OAT1 internalization and degradation.